A case study of out-of-school language practice with implications for language teaching and policy - (:unkn) unknown (My University, 2012)
http://www.ifas.org.za/research/2012/lesedi-14-july-2012/The language component of any education policy orcurriculum is vital since language – understood educationallyas a capacity to read, write and talk without error whilstincorporating cultural knowledge – is both a skill in itself andwhat essentially provides access to other content subjects. InSouth Africa the question of language becomes, rightly, aquestion of politics and distributive justice since instruction ismuddied by the gross unfairness of the now defunct BantuEducation Act (1953), and the contemporary transition to amore democratic educational dispensation. Whilst SouthAfrica does recognise eleven official languages and wouldseem to promote linguistic diversity, there is still a rift betweenpolicy and praxis that hinges upon a growing need to see theworld from the global South (Nuttall and Mbembe, Eds., 2008),as a heterogeneous place, with its own realities. The doubleimportance of language in education can be resumed undertwo considerations, namely that a) language is a medium ofinstruction which enables and constrains learning ininstitutions; and b) language is itself taught as a subject withgreater or lesser effect. The aim of this article is to presentfindings from a case study which, by drawing on broaderresearch into informal (out-of-school, non-institutional)contexts of writing, has decided interest for the firstconsideration and may help to draw some conclusions for thesecond, at least insofar as the teaching of English isconcerned.Documentation such as that recently issued by the DoBEi(1997 and 2010) on the status of languages in South Africanpublic schools, provides a compelling entry into the debate.On the one hand a policy designed to allow multilingualism,and on the other a clear preference for English as LOLT which iigives an image of ill-controlled language dominance.Reinforcing this negative image is clear systemic dysfunctionwhere, for instance, there is only 0.9% En
Keywords: African Research